Micro-Enterpreneur in Bali Communicate Messages and Brand Values To Influence Brand Image Effectively - Adinda Soraya; Indra Novianto Adibayu Pamungkas (Eduvest - Journal of Universal Studies, 2025)
This study explores the communication identity of micro-merchants in Bali and its influence on brand image. Using a qualitative approach within a constructivist paradigm, it examines how micro-merchants craft their communication identity in Bali’s unique social and cultural environment. Data collection methods included in-depth interviews, participatory observation, and document analysis, while NVivo 12 software was utilized to analyze themes and patterns. The findings reveal that micro-merchants’ communication identities are deeply rooted in personal values, cultural preservation, strong customer relationships, and community engagement. Key personal values such as integrity and customer satisfaction are prioritized, alongside efforts to maintain and showcase Balinese culture in their business practices. Furthermore, VOSviewer software visualized thematic networks linking communication identity and brand image, offering insights into their interconnectedness. Based on the results, this study recommends enhancing customer communication, providing modern marketing training, and fostering collaboration networks to ensure business sustainability. These steps can empower micro-merchants to strengthen their brand image while maintaining cultural authenticity. Future research should focus on developing business models that integrate cultural values with sustainable business practices, offering a framework for micro-merchants to thrive in competitive markets while preserving Bali's rich heritage.